도심 공원 안전도와 공원 평판 제고를 위한 유명인 팬클럽의 기여도 연구 - 윤천석 (한국설비안전학회지, 2021)
The role of city parks has become increasingly important as people work with more technologies while having less contact with nature and people. In addition to its mission of promoting people’s welfare, city parks are designed to preserve the natural environment and help people lower their stress for such as the quality of life and work safety. Scientists insist that the Corona pandemic is a direct outcome of the environmental contamination and climate change. Under the increasing pressure for such causes, the role of urban parks is reemphasized both domestically and globally. This study looked into how the safety perception, reputation and attitude of urban parks can be enhanced. This study focuses particularly on the relationship between park safety perceptions and park visitation as the park safety is one of the major decision factors for park visitation. Past literature shows that the stress level of employee’s life has an significant impact on the prevention of industrial safety accidents. The three dependant variables were suggested using three experimental media articles. The first one was presented for measuring park's current perceptions. The second experimental article shows that a celebrity fan club built a small garden with a bench and flowers under the celebrity name in an urban park. The third article depicts that the celebrity small garden is mismanaged. The results show that the presence of celebrity garden representing the celebrity effects uplifts the safety perception, reputation and attitude of park. However, when the celebrity inner garden was poorly managed, all three dependent variables were lowered significantly. Getting a celebrity fan club involved in the park campaign is an effective way for elevating the citizen’s perceptions of park safety, reputation and attitude. This study further testifies that cooperating with a celebrity fan club for park campaign is an innovative marketing scheme in terms of cost-saving and public relations.
Keywords: Park Safety Perception; Reputation of Park; Celebrity Effects; Attitude of Park